Flexibility of an Open Indenyl Ligand in Iron(II) Complexes - Gloeckner, Andreas; Bannenberg, Thomas; Ibrom, Kerstin; Daniliuc, Constantin G.; Freytag, Matthias; Jones, Peter G.; Walter, Marc D.; Tamm, Matthias (Organometallics, 2012)
[FeI2(thf)(2)] was sequentially treated with Li(C5Me5) and the potassium salt of the phenylmethallyl ("open indenyl") ligand oIndme, leading to selective formation of the half-open ferrocene [(eta(5)-C5Me5)Fe(eta(5)-oInd(Me))] (1). A variable-temperature NMR study revealed a barrier of ca. 12 kcal mol(-1) for the rotation of the phenyl group. The apparent lability and susceptibility of the oIndme ligand in 1 to undergo PIS 113 interconversion allowed the preparation of the complexes [(eta(5)-C5Me5)Fe(eta(3)-oInd(Me))(L)] (2, L = CO; 3, L = IMe; 4, L = PMe3) by addition of carbon monoxide, 1,3,4,5-tetramethylimidazolin-2-ylidene (IMe), and trimethylphosphine, respectively. The eta(3)-bound phenylmethallyl ligand in these complexes initially adopts an anti orientation with regard to the relative positions of the phenyl and methyl substituents, followed by anti-to-syn isomerization. For L = CO, both isomers could be isolated, and the conversion of anti-2 into syn-2 was monitored by NMR spectroscopy at 35, 50, 65, and 80 degrees C, affording an enthalpy of activation of Delta H double dagger = 24(1) kcal mol(-1) for this equilibrium reaction. On the basis of DFT calculations, a mechanism is proposed that proceeds via consecutive eta(3)-eta(1)-eta(3) interconversions and involves eta(3)-benzyl intermediates. In contrast, rapid equilibration was observed for L = IMe and PMe3. Addition of 1,2-bis(dimethylphosphino)ethane (dmpe) to 1 gave (eta(5)-C5Me5)Fe(eta(1)-oInd(Me))(dmpe)] (5), containing the oIndme ligand bound in an eta(1)-allyl fashion, eta(5)-to-eta(3) hapticity interconversion was also observed upon reaction of 1 with methyl iodide and CH2Cl2, which formed the Fe(III) complexes [(eta(5)-C5Me5)Fe(eta(3)-oInd(Me))(X)] (6, X = 1; 7, X = Cl); solid-state magnetic susceptibility measurements on 6 revealed an S = 1/2 ground state. The mixed indenyl open indenyl complex [(eta(5)-Ind")Fe(eta(3)-oInd(Me))(CO)] (9, Ind '' = 1,3-di(tert-butyl)indenyl) was isolated from the stepwise reaction of [FeI2(thf)2] with Na(Ind ''), K(oInd(Me)), and CO. The molecular structures of 1, anti-2, syn-2, syn-3, 5, syn-6, syn-7, and syn-9 were established by single-crystal X-ray diffraction.